ANALYZING THE INFLUENCING FACTORS OF CUSTOMER LOYALTY FROM OMOLAS BARBERSHOP IN MANADO - Trygen Maurits Antariksa Kuera; Willem J. F. A. Tumbuan; Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this study is to analyze service quality, customer experience, customer trust, pricing, payment method, brand perception, product variety, brand trust, brand equity, customer commitment, peer group influences, switching cost, facilities, differentiation strategy, lifestyle, and brand benefit and their influence on the customer loyalty in Omolas Barbeshop in Manado. This research uses a quantitative approach with descriptive research. The data analysis method used in this research is Exploratory Factor Analysis (EFA). The researcher distributed questionnaires, and the sample used was 30 respondents. The results of service quality, customer experience, customer trust, pricing, payment method, brand perception, product variety, brand trust, brand equity, customer commitment, peer group influences, switching cost, facilities, differentiation strategy, lifestyle, and brand benefit simultaneously have a significant influence on customer loyalty in Omolas Barbershop in Manado. Partially, customer trust, brand perception, and customer commitment have influence on customer loyalty, so barbershop should consider to develop appropriate marketing and service strategies to build strong and long-term relationships with consumers, thereby increasing the level of consumer loyalty.                                                                                                                                                                                                    Keywords: customer satisfaction, exploratory factor analysis